Relationship satisfaction as correlates to academic self-confidence among gay and lebian college students: basis for a proposed gay and lesbian relatedness program - Almira Joy A. Abanto, Jade Louie M. Bernabe, Micah Eunice I. Duque, Vince Cezar G. Madriaga and Corinne Glo C. Panahon. 4 0 16; 5 (2023)
u
Undergraduate Thesis: Bachelor of Science in Psychology, Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2